2008
DOI: 10.1007/s00018-008-8383-9
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced autophagy and apoptosis are mediated by a calcium signaling pathway

Abstract: The cytotoxicity of cadmium (Cd) induced autophagy and apoptosis in MES-13 cells was determined by flow cytometry. Autophagy was also assessed by formation of autophagosomes and processing of LC3. Pharmacological inhibition of autophagy resulted in increased of cell viability, suggesting autophagy plays a role in cell death in Cd-treated mesangial cells. Cd also induced a rapid elevation in cytosolic calcium ([Ca(2+)](i) ), and modulation of [Ca(2+)](i) via treatment with IP (3)R inhibitor or knockdown of calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
140
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(154 citation statements)
references
References 66 publications
12
140
2
Order By: Relevance
“…The binding of Bcl-2 to IP3-R hampers the efflux of Ca 21 from the ER (Pattingre et al, 2005;Høyer-Hansen et al, 2007), and the overexpression of ER-targeted Bcl-2, but not Bcl-2 targeted to the mitochondria, stabilizes the complex and inhibits autophagy that depends on Ca 21 from the ER (Criollo et al, 2007). Corroborating this, the phosphorylation of Bcl-2 by JNK during starvation and after treatment with IP3-R antagonists releases BECN1 and allows the initiation of autophagy (Wang et al, 2008;Vicencio et al, 2009). The knockdown of IP3-R also leads to an accumulation of autophagosomes in HeLa cells.…”
Section: Autophagy Ca 21 and Cancermentioning
confidence: 99%
“…The binding of Bcl-2 to IP3-R hampers the efflux of Ca 21 from the ER (Pattingre et al, 2005;Høyer-Hansen et al, 2007), and the overexpression of ER-targeted Bcl-2, but not Bcl-2 targeted to the mitochondria, stabilizes the complex and inhibits autophagy that depends on Ca 21 from the ER (Criollo et al, 2007). Corroborating this, the phosphorylation of Bcl-2 by JNK during starvation and after treatment with IP3-R antagonists releases BECN1 and allows the initiation of autophagy (Wang et al, 2008;Vicencio et al, 2009). The knockdown of IP3-R also leads to an accumulation of autophagosomes in HeLa cells.…”
Section: Autophagy Ca 21 and Cancermentioning
confidence: 99%
“…28 In this respect, other groups proposed Ca 2+ dependence for protein kinase Cθ (PKCθ) in ER stress-induced autophagy, 30 or for extracellular signal regulated kinase (ERK) in Cd 2+ -induced autophagy. 29 …”
Section: +mentioning
confidence: 99%
“…68 Similarly, compounds such as thapsigargin and alisol B that inhibit the action of ATP2A (ATPase, Ca 2+ transporting, cardiac muscle), prevent ER Ca 2+ uptake and thereby maintain elevated [Ca 2+ ] C , inducing autophagy. 25,48,52,54 Finally, Sakaki et al 69 established that PRKCQ (protein kinase C theta) is required for ER stress-induced autophagy. Increased [Ca 2+ ] C induces PRKCQ phosporylation and its localization to cytosolic MAP1LC3 puncta.…”
Section: + As An Autophagy Triggermentioning
confidence: 99%
“…43,44,53 Finally, in a separate study, rapid elevation in [Ca 2+ ] C induced by extracellular cadmium was found to trigger autophagy via the MAPK1/3 (mitogen-activated protein kinase 1/3) pathway, although crosstalk between MAPK1/3 and MTOR signaling cascades has recently been proposed. 54,55 Besides cadmium, various external stimuli have been reported to trigger autophagy by elevating cytosolic Ca 2+ concentrations. First, exogenous Ca 2+ phosphate precipitates have been observed to induce autophagy, as demonstrated both by the formation of MAP1LC3 puncta, a phenomenon fundamentally associated with the formation of autophagic vesicles, and by the conversion of cytosolic MAP1LC3-I to the autophagosome-associated MAP1LC3-II form.…”
Section: + As An Autophagy Suppressormentioning
confidence: 99%